2021
DOI: 10.1186/s13741-021-00189-1
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative digital behaviour change interventions for reducing alcohol consumption, improving dietary intake, increasing physical activity and smoking cessation: a scoping review

Abstract: Background Evidence suggests that unhealthy lifestyle behaviours are modifiable risk factors for postoperative complications. Digital behaviour change interventions (DBCIs), for instance text messaging programs and smartphone apps, have shown promise in achieving lifestyle behaviour change in a wide range of clinical populations, and it may therefore be possible to reduce postoperative complications by supporting behaviour change perioperatively using digital interventions. This scoping review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…One feature of digitally enabled healthcare is the ability to provide support to patients to attempt to minimise the complexity of pathways, enhance engagement with the clinical plan and prompt patients to attend investigations and appointments. This approach is supported by published data showing improved outcomes across a range of conditions including COPD (38), diabetes (39) and the perioperative journey (40). The applicability of these interventions is striking when deployed to help manage long-term conditions.…”
Section: The "Clinical Concierge" and Long Term Conditionsmentioning
confidence: 83%
See 1 more Smart Citation
“…One feature of digitally enabled healthcare is the ability to provide support to patients to attempt to minimise the complexity of pathways, enhance engagement with the clinical plan and prompt patients to attend investigations and appointments. This approach is supported by published data showing improved outcomes across a range of conditions including COPD (38), diabetes (39) and the perioperative journey (40). The applicability of these interventions is striking when deployed to help manage long-term conditions.…”
Section: The "Clinical Concierge" and Long Term Conditionsmentioning
confidence: 83%
“…Not all patients attending clinic appointments will be employed either due to them being too young to work or being retired, additionally not all the working age population are employed. To adjust the figures accordingly the total number of appointments attended by patients between the age of 20 and 64 can be ascertained from NHS digital's hospital outpatient activity data 2020-21 (40,873,275) and then multiplied by the UK employment rate in 2021 (96.4%) to give a total of 39,401,837 appointments. Therefore, by using the adjusted attendance figures and estimated loss of GVA, it can be calculated that approximately £3.4 billion was lost from the UK economy as a direct consequence of outpatient appointments attended in 2021-2022.…”
Section: Reduction In Gva Lossmentioning
confidence: 99%
“…Reviews (and a recent umbrella review [26]) of prehabilitation interventions addressing health risk behaviours have been conducted. However, these have focused on just one or two health behaviours [27][28][29], have been restricted to digital interventions [30] or have focused on special clinical groups (i.e., bariatric surgery [30], patients with alcohol dependency [26]). Further, no previous reviews have sought to examine the impact of prehabilitation interventions by health inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, prehabilitation is commonly delivered face to face, with a focus on exercise training, nutrition and well-being 21. Very few studies have reported outcomes from a personalised, digitally delivered programme targeting multiple behaviours adapted to patient need 22. Digital interventions are being increasingly recommended to facilitate healthcare delivery and support perioperative care 23–25.…”
Section: Introductionmentioning
confidence: 99%
“…21 Very few studies have reported outcomes from a personalised, digitally delivered programme targeting multiple behaviours adapted to patient need. 22 Digital interventions are being increasingly recommended to facilitate healthcare delivery and support perioperative care. [23][24][25] They have matched face-to-face delivery in supporting behaviour change in other healthcare settings such as cardiac rehabilitation and diabetes management.…”
Section: Introductionmentioning
confidence: 99%